2019
DOI: 10.3390/nano9050685
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Performance of ZnO Doped Tantalum Oxide Multilayer Composite Coatings on Ti6Al4V for Orthopedic Application

Abstract: Ti6Al4V titanium alloy has been widely used as medical implant material in orthopedic surgery, and one of the obstacles preventing it from wide use is toxic metal ions release and bacterial implant infection. In this paper, in order to improve corrosion resistance and antibacterial performance of Ti6Al4V titanium alloy, ZnO doped tantalum oxide (TaxOy) multilayer composite coating ZnO-TaxOy/TaxOy/TaxOy-TiO2/TiO2/Ti (ZnO-TaxOy) was deposited by magnetron sputtering at room temperature. As a comparison, monolaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 81 publications
(105 reference statements)
0
17
0
Order By: Relevance
“…The bonding mechanism between the coating and the substrate is complicated, and the bonding strength can be affected by many factors, such as the surface state of the substrate, preparation parameters, substrate temperature, intermediate layer, coating thickness, post-heat treatment [1,4,29,70], etc. For a multilayer Cu-MTa 2 O 5 coating, its adhesion strength is higher than that of the single layer Ta 2 O 5 coating due to the introduction of the multiple intermediate layers of Ta 2 O 5 -TiO 2 /TiO 2 /Ti.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bonding mechanism between the coating and the substrate is complicated, and the bonding strength can be affected by many factors, such as the surface state of the substrate, preparation parameters, substrate temperature, intermediate layer, coating thickness, post-heat treatment [1,4,29,70], etc. For a multilayer Cu-MTa 2 O 5 coating, its adhesion strength is higher than that of the single layer Ta 2 O 5 coating due to the introduction of the multiple intermediate layers of Ta 2 O 5 -TiO 2 /TiO 2 /Ti.…”
Section: Resultsmentioning
confidence: 99%
“…Ti6Al4V titanium alloy, as a medical implant material, has been commonly applied in dentistry, orthopedics, and other fields due to its excellent corrosion resistance, mechanical properties, and biocompatibility [1,2,3,4]. However, clinical studies have indicated that Ti6Al4V titanium alloy-related implants would be corroded by body fluids, releasing toxic and side-effectmetal ionssuch as V 5+ and Al 3+ [5,6], and causing local immune dysfunction [7], inflammation, and cytotoxic reactions in the human body [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ding et al . [ 203 ] studied about the properties of ZnO doped tantalum oxide (Ta x O y ) multilayer composite coatings on Ti6Al4V. The scratch test was done to examine the adhesion strength between the deposited coating and substrate.…”
Section: Common Failures In Zno Thin Film Coatingmentioning
confidence: 99%
“…On the surface of Ti6Al4V, Ding et al successfully prepared a ZnO-doped tantalum oxide multilayer composite coating (ZnO-Ta x O y ) by magnetron sputtering which showed that the ZnO-Ta x O y coating has great potential in improving the corrosion resistance and antimicrobial performance of Ti6Al4V implants. However, the cytocompatibility and optimal design of ZnO-Ta x O y coatings (e.g., composition, coating thickness, preparation parameters) need to be further improved [ 67 ].…”
Section: Fabrication Of Nano-zno Modified Ti Materials and Their Biosafe Propertiesmentioning
confidence: 99%
“…In a study, a ZnO-doped tantalum oxide (Ta x O y ) multilayer composite coating was deposited by magnetron sputtering at room temperature. The potentiodynamic polarization curves revealed that ZnO-doped multilayer composite coating had higher corrosion potential and lower corrosion current density (1.12 ± 0.004 µA/cm 2 ) than that of Ta x O y coating, showing better corrosion inhibition [ 67 ]. Roknian et al indicated that the corrosion current density had a 93% reduction for the sample containing ZnO nanoparticles at a concentration of 15 g/L in comparison with the uncoated Ti substrate [ 58 ].…”
Section: Anti-corrosion Property Of Nano-zno Modified Ti Implantsmentioning
confidence: 99%